Sub-national Revenue Mobilization in Mexico - Luis Cesar Castaneda; Juan Pardinas (Inter-American Development Bank (IDB), 2012)
This paper estimates potential Mexican sub-national tax revenues using a stochastic frontier model. The results suggest that states are exploiting their current tax bases, particularly the payroll tax, appropriately. Mexican municipalities, however, have a low rate of tax collection compared to their potential, especially in relation to the property tax, which is their most important source of revenue and relatively simple to collect. Empirical evidence further suggests that tax collection efforts are strongly related to GDP per capita, and that some political economy factors can influence them. Political affiliation, for example, influences municipalities' tax collection effort more than that of states. The analysis of a scenario in which some VAT and PIT taxation powers are returned to the states suggests that a state surcharge on the VAT and PIT could increase states' own revenues. Without broadening the tax base and redefining the revenue-sharing allocation criteria, however, doing so would have a strong and adverse impact on the revenue distribution of sub-national governments.
Keywords: H3; H7; H71; 330